2011
DOI: 10.1111/j.1939-1676.2011.0728.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Acute Phase Proteins as Clinical Phase Indicators and Outcome Predictors in Naturally Occurring Canine Monocytic Ehrlichiosis

Abstract: Background: Canine monocytic ehrlichiosis (CME), caused by Ehrlichia canis, is an important tick‐borne disease of global importance. Currently, limited information is available on the diagnostic and prognostic value of acute phase proteins (APPs) in dogs naturally infected with E. canis. Hypothesis: APPs may be useful indicators of the clinical phase of CME and predictive of the clinical outcome (death or survival). Animals: Fifty‐six dogs naturally infected with E. canis and 7 clinically healthy control do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 29 publications
5
60
0
3
Order By: Relevance
“…The reason for higher concentrations of SAA in septic dogs may be related to inflammatory reactions and tissue damage. Similary, several studies have reported that CRP and SAA could be useful markers for diagnosis and prognosis in various disease [10,16,17,34,35] . However, CRP and SAA do not seem to be very spesific markers for the detection of bacterial infections because it might increase in a variety of diseases, not particularly in bacterial infections [10,16,17,35] .…”
Section: Discussionmentioning
confidence: 97%
“…The reason for higher concentrations of SAA in septic dogs may be related to inflammatory reactions and tissue damage. Similary, several studies have reported that CRP and SAA could be useful markers for diagnosis and prognosis in various disease [10,16,17,34,35] . However, CRP and SAA do not seem to be very spesific markers for the detection of bacterial infections because it might increase in a variety of diseases, not particularly in bacterial infections [10,16,17,35] .…”
Section: Discussionmentioning
confidence: 97%
“…In naturally occurring canine monocytic ehrlichiosis while raised concentrations were found for CRP, SAA and Hp on admission, there was no predictive value for the clinical outcome from the levels found [35]. Nevertheless, CRP and Hp were higher in dogs with the myelosuppressive form (chronic), thus being useful indicators of the clinical phase of the disease.…”
Section: Dogsmentioning
confidence: 88%
“…πετέχειες και εκχυμώσεις στο δέρμα και στους βλεννογόνους, ύφαιμα, επίσταξη, ουλορραγία, αιματουρία), είναι συχνές κλινικές εκδηλώσεις στη ΜΕΣ, αν και με διαφορετική συχνότητα και βαρύτητα μεταξύ των φάσεων της νόσου (Komnenou et al 2007, Mylonakis et al 2011. Η θρομβοκυτταροπενία και η αναιμία είναι οι συχνότερες αιματολογικές διαταραχές, με την απλαστική παγκυτταροπενία να χαρακτηρίζει τη μυελοκατασταλτική μορφή της ΜΕΣ (Mylonakis et al 2011). Στις συχνότερες βιοχημικές διαταραχές περιλαμβάνονται η υπερσφαιριναιμία, η υπολευκωμα-τιναιμία και η αυξημένη δραστηριότητα των ηπατικών ενζύμων (Μylonakis et al 2011).…”
Section: εισαγωγηunclassified